Sustainable urban regeneration: GIS and hedonic pricing method in determining the value of green space in housing area - Hj. Mohd. Noor, Norzailawati; Asmawi, M. Zainora; Abdullah, Alias (Elsevier, 2015)
This paper explores a framework that combines Geographic information System (GIS) with Hedonic pricing method in improving the analysis and determining the value of green spaces with housing prices in Subang Jaya, Malaysia. The previous study found that proposed combination between GIS and Hedonic pricing method for the same purpose has not been fully explored particularly in Malaysia. Findings show the proposed combined method leads to an improved understanding and representation of urban dynamics and regeneration process, furthermore will encourage a sustainable setting of the environmental amenities in improving the geospatial technologies respectively.